Analisis Ekonomi Islam Terhadap Transaksi Pembiayaan Griya Dengan Menggunakan Akad Murabahah Di Bsm Cabang Situbondo - Rasuli (Lembaga Pusat Penelitian dan Pengabdian kepada Masyarakat (LP2M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2021)
This study was conducted at the Bank Mandiri Syariah (BSM) Situbondo Branch, with the conclusion that BSM is a bank with fairly reliable management, allowing it to survive and compete with non-Islamic (conventional) banks. BSM has many features and cooperation programs, including cooperation in the purchase of homes on credit, namely Griya financing products. Griya BSM financing is a murabahah-based short, medium, or long-term loan used to fund the acquisition of new and old residential (consumer) properties in a developer context. The practice of griya financing using murabahah agreements in BSM Situbondo Branch, Islamic Economic Analysis of griya financing using murabahah agreements in BSM Situbondo Branch, and Risk management Analysis of griya financing using murabahah agreements in BSM Situbondo Branch are the limitations of the problems used in this study. This study came to various conclusions, such that implementing griya financing transactions at BSM KCP Situbondo in the context of Fikih Mu'amalah is less acceptable when employing murabahah agreements, and that it is preferable to use the rahn account, according to the author. Keywords: Griya; Murabahah; Islamic Bank